JAG2 signaling induces differentiation of CD14+ monocytes into Langerhans cell histiocytosis-like cells. Issue 1 (8th October 2018) - Schwentner, Raphaela; Jug, Gunhild; Kauer, Maximilian O; Schnöller, Thomas; Waidhofer-Söllner, Petra; Holter, Wolfgang; Hutter, Caroline
Abstract: Langerhans cell histiocytosis (LCH) is a MAPK pathway-driven disease characterized by the accumulation of CD1a + langerin + cells of unknown origin. We have previously reported that the Notch signaling pathway is active in LCH lesions and that the Notch ligand Jagged2 (JAG2) induces CD1a and langerin expression in monocytes in vitro. Here we show that Notch signaling induces monocytes to acquire an LCH gene signature and that Notch inhibition suppresses the LCH phenotype. In contrast, while also CD1c + dendritic cells or IL-4-stimulated CD14 + monocytes acquire CD1a and langerin positivity in culture, their gene expression profiles and surface phenotypes are more different from primary LCH cells. We propose a model where CD14 + monocytes serve as LCH cell precursor and JAG2-mediated activation of the Notch signaling pathway initiates a differentiation of monocytes toward LCH cells in selected niches and thereby contributes to LCH pathogenesis. This study aims to identify the cell of origin of Langerhans Cell Histiocytosis and the molecular mechanisms of its pathogenesis.